Pengaruh Kualitas Informasi E-Katalog Dan Kualitas Layanan Chatbot Terhadap Pengalaman Pembelian Pelanggan Pada Toko Online Arogansociety - Farhan Nur Triwibowo; Ati Hermawati (Universitas Pakuan, 2026)
The Effect of E-Catalog Information Quality and Chatbot Service Quality on Customer Purchase Experience at Arogansociety Online Store This study aims to analyze the effect of e-catalog information quality and chatbot service quality on customer purchase experience at the Arogansociety online store. This research employs a quantitative approach using a causal associative method. Data were collected through questionnaires distributed to 100 respondents who are Arogansociety customers using purposive sampling technique. Data analysis was conducted using SPSS, including validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing both partially (t-test) and simultaneously (F-test). The results indicate that e-catalog information quality has a positive and significant effect on customer purchase experience. Chatbot service quality also has a positive and significant effect on customer purchase experience. Simultaneously, e-catalog information quality and chatbot service quality have a positive and significant effect on customer purchase experience. These findings suggest that better information quality and optimized chatbot services can significantly enhance customer purchase experience. This study implies that business actors, particularly Arogansociety, should improve the quality of e-catalog information and optimize chatbot services to create a better purchase experience, increase customer satisfaction, and foster customer loyalty.programs.